Visual Studio code for C# developers (Packt Publishing, 2022)
Learn the most in-demand IDE currently among the programmers’ community. Acquire the skill of editing the source code in an efficient way, especially inclined towards C# developers. Visual Studio Code is the #1 IDE among the programmers’ community. The usage of VS Code has increased exponentially in recent years. Companies such as Facebook, Google, Microsoft, and many others use Visual Studio Code to do development in various programming languages at a large scale. You will be learning these VS Code concepts from scratch in this course. You will get started with Visual Studio Code and create your first C# project. Then master editing and know how to navigate better in Visual Studio Code. After that, you will get to know Intellisense and use extensions in VS Code. Post that, you will learn to debug in Visual Studio Code, and master Git and GitHub usage for your C# projects. Finally, you will learn Visual Studio Code workspaces, and build snippets in Visual Studio Code. By the end of this course, you will have a strong foundation in using Visual Studio Code for C# programming. This course will provide significant knowledge of using Visual Studio Code for your next C# project. You will be certain to use the learned concepts with ease by following a step-by-step approach. You will be confident to instantly apply the IDE tips covered in the course.